Trends in Methodological Designs in Indexed Publications on Job Satisfaction of University Professors - Limaymanta-Álvarez, César Halley (2019)
This study aims to perform a systematic review of the trends of the methodological design used in research articles whose main theme is the job satisfaction of the university teaching staff. The trends on the research method, the condition of the measurement instrument, the techniques for the collection of information, the sampling techniques, and the statistical techniques used in the analysis are identified. After a systematic search in Proquest and Redalyc (bibliographyc databases), according to inclusion and exclusion criteria, 49 articles published between 2000 and 2016 were analyzed. This review allowed us to identify that almost half of the articles selected belong to the last six years (44.9%), which reveals a great interest in the subject. The most frequent methodological approach is the quantitative one (89.8%), the adaptation of the instruments predominates (53.1%), and the psychometric properties of validity and reliability are mentioned at 42.9%. A probabilistic and non-probabilistic sampling is used with the same frequency (36.7%); likewise, descriptive statistics are used in 83.3%. However, for the inferential analyses, there was greater use of parametric statistical tests than nonparametric ones. The results show that there are multiple ways to carry out the methodological design, both in the use of the data collection instrument and in the use of information analysis methods.